PUERPERAL MASTITIS COMPLICATED WITH MYIASIS: A CASE REPORT - Pachnicki, Jan Pawel Andrade; Meschino, Alice Soares Paes Giugliano; Kilian, Fernanda Cristina; Moraes, Gabriela Vanim de; Lima, Sarah Oliveira de (Mastology, 2021)
Introduction: Puerperal mastitis is an inflammatory process of the mammary gland that affects women during lactation, due to stasis in the mammary ducts. The clinical findings vary from focal inflammation to abscesses when not treated early. Additional complications may arise, such as tissue loss by necrosis, leading to the appearance of opportunistic diseases. Myiasis consists of appearance of fly larvae in these tissues, a rare condition in humans. When in cutaneomucosal area, there are complaints of intense pruritus and local pain. The authors seeked to correlate the clinical aspects of puerperal mastitis with breast involvement by myiasis, aiming at the importance of early management and treatment of these pathologies. Case report: A 23-year-old patient, GIV PIII, was admitted to a maternity hospital in Paraná, Brazil, with mastitis. The day after the admission, under treatment with Oxacillin, she evolved to natural birth. During the immedi - ate puerperium, abscedation was observed, and surgical drainage was indicated. The patient refused to be submitted to the procedure and evaded the hospital. One week later, she returned with an engorged, edematous and hyperemic right breast, with fluctuation point at 2h and spontaneous drainage of purulent secretion, in addition to a subareolar hematoma. The patient was submitted to drainage, surgical debridement, removal of the myiasis larvae noticed in the mam - mary tissue, and placement of a drain. Material sent for culture demonstrated growth of Staphylococcus epidermidis; deescalating broad-spectrum antibiotic regimen started empirically when she was admitted, associated with Ivermectin and Cabergoline. She presented a satisfactory response of the inflammatory process, though dehiscence of the surgical wound occurred, and she was submitted to reconstruction with breast flap during reoperation. The diagnosis of mastitis is based on breast tenderness, local flogistic signs, decreased lactopoiesis, associated with fever and fatigue, and among its serious complications is the breast abscess. The patient presented a unilateral mastitis complaining of pain, edema, local heat and hyperemia, in addition to periareolar purulent discharge and abscedation, suggesting complicated puerperal mastitis. However, because the case was not immediately resolved, the clinical situation deteriorated, with perimammary necrosis and myiasis. The necrosed tissue facilitated the penetration of larvae, a determining factor for this coinfection. It is prevalent in developing countries with poor sanitary conditions, and open wounds or necrosis are more favorable for the growth of larvae. It is necessary to emphasize the importance of good personal hygiene and adequate clothes’ washing, especially in endemic areas of myiasis, to avoid this complication and its late diagnosis.